Feminism In The Adaptation Of Brothers Grimm’s Little Snow White Into Movie - Sampurna, Hadi; Salindri, Intan; Priya, R. Lakshmi (Pusat Studi Gender Universitas Jember, 2024)
The aim of this study is to identify changes in ideology on character and the plot in the adaptation of the fairy tale Little Snow White by Brothers Grimm. The research data consists of narrative texts from the fairy tale and visual scenes from the movie adaptation. The data are analyzed with comparative approach and Barthes' semiotics theory. In addition, the visual scenes are analyzied with cinematography and mise en scene approach. The findings show the changes of ideology in the fairy tale into movie adaptation. The dominant ideology of fairy tales is patriarchy, which emphasizes gender inequality, women oppression, and damsels in distress. Other than patriarchy, the fairy tale's ideology is Eurocentrism. Meanwhile, the movie adaptation depicts a variety of ideologies, namely cultural racism, feminism, radical-libertarian feminism, and androgyny; however, upon closer inspection, feminism emerges as the dominant ideology